1998
DOI: 10.1515/jpem.1998.11.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Lumbar Spine Bone Mass and Low Bone Turnover in Children and Adolescents with Insulin Dependent Diabetes Mellitus Followed Longitudinally

Abstract: The effects of insulin dependent diabetes mellitus (IDDM) on bone metabolism are still not well defined. We evaluated total bone mineral content (TBMC) and bone mineral density (BMD) at the lumbar spine and femoral neck using dual X-ray absorptiometry in 26 IDDM children (15 M, 11 F) with a mean chronological age of 12.1+/-3.1 yr (range 7.1-14.2 yr). Duration of diabetes was 4.3+/-2.9 yr, with a mean glycosylated hemoglobin of 9.2+/-0.4%. BMD and TBMC standard deviation scores (Z-scores) were determined by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
92
1
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 21 publications
18
92
1
11
Order By: Relevance
“…Some studies, however, documented the presence of osteopenia at diagnosis of diabetes (35). As depicted in Table 1, BMD correlated poorly with glycaemic control in most (29,33,34,35,36,37), but not all (28,31,32), studies. However many studies reported an association between the presence of microvascular complications of diabetes and the presence and/or progression of a decreased BMD (27,28,38,40,42,50).…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies, however, documented the presence of osteopenia at diagnosis of diabetes (35). As depicted in Table 1, BMD correlated poorly with glycaemic control in most (29,33,34,35,36,37), but not all (28,31,32), studies. However many studies reported an association between the presence of microvascular complications of diabetes and the presence and/or progression of a decreased BMD (27,28,38,40,42,50).…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
“…Although the decreased BMD reported in subjects with T1DM (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,50,58) may largely explain the higher fracture risk observed in these patients (17,18,19,20,21,22,26), alterations in bone quality, as described below, may also contribute and actually confer its specific nature to diabetic bone disease.…”
Section: Quantitative and Structural Bases Of Bone Fragilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In pediatric patients, in particular, this method has l i m i t a t i o n s b e c a u s e o f t h e t w odimensional measurement and therefore height dependency. Longitudinal data on relatively small numbers of patients over 2-4 years revealed disturbed or normal bone development (7,8). A recently published study over a wide time range from 12 to 84 months showed slightly reduced mineralization of the spine independent of metabolic control or microvascular complications (9).…”
mentioning
confidence: 94%